2007
DOI: 10.1111/j.1469-8986.2007.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential processing of interaural timing differences for sound source segregation and spatial localization: Evidence from event‐related cortical potentials

Abstract: Cortical processing of interaural timing differences (ITDs) was investigated with event-related potential (ERP) measurements in 16 human participants who were required in separate tasks to detect or to spatially localize dichotically embedded pitches. ITDs elicited three ERP components labeled ORN, N2, and P400. The ORN occurred at a latency of 150-250 ms and was elicited by ITDs regardless of location or task. In contrast, the N2 response (250-350 ms) was strongly modulated by location and showed larger ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…In active listening situations, ORN elicitation is accompanied by a late positive wave that peaks about 400 ms after stimulus onset, the P400 component. P400 amplitude also correlates with the likelihood of perceiving two concurrent sound objects compared to one (Alain et al, 2001(Alain et al, , 2002Hautus & Johnson, 2005), but P400 does not follow the ORN in an obligatory manner (Johnson, Hautus, Duff, and Clapp, 2007). Johnson et al (2007) proposed that P400 is influenced by the task context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In active listening situations, ORN elicitation is accompanied by a late positive wave that peaks about 400 ms after stimulus onset, the P400 component. P400 amplitude also correlates with the likelihood of perceiving two concurrent sound objects compared to one (Alain et al, 2001(Alain et al, , 2002Hautus & Johnson, 2005), but P400 does not follow the ORN in an obligatory manner (Johnson, Hautus, Duff, and Clapp, 2007). Johnson et al (2007) proposed that P400 is influenced by the task context.…”
Section: Introductionmentioning
confidence: 99%
“…P400 amplitude also correlates with the likelihood of perceiving two concurrent sound objects compared to one (Alain et al, 2001(Alain et al, , 2002Hautus & Johnson, 2005), but P400 does not follow the ORN in an obligatory manner (Johnson, Hautus, Duff, and Clapp, 2007). Johnson et al (2007) proposed that P400 is influenced by the task context. In their study, they used two different tasks: In the detection task, participants were to indicate whether they heard dichotic pitch or a control stimulus, whereas in the localization task, only dichotic pitch stimuli were presented, and participants were to decide where the sound was located.…”
Section: Introductionmentioning
confidence: 99%
“…The supratemporal plane has been shown to process binaural cues in the context of auditory streaming (Schadwinkel and Gutschalk 2011), potentially as early as 60 ms after a sound is encountered (Johnson et al 2007). The posterior inferior frontal cortex, which has also been implicated in position-linked sound processing, is within a region known to be selective for non-spatial processing (Maeder et al 2001;Cohen et al 2009) but receives convergent input from the ventral and dorsal streams (Romanski et al 1999a;Frey et al 2014;Frey et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At 150-200 ms after stimulus onset, a negative deflection is observed during the processing of ITD in dichotic pitch discrimination (Johnson et al 2003;Alain et al 2001b;Alain et al 2002). The location of the dichotic pitch, in left versus right hemispace, modulates the N2 response that occurs 250-350 ms after stimulus onset (Johnson et al 2007), and selective attention modulates the neural activity at 400-500 ms (Hautus and Johnson 2005). Taken together, these results indicate that ITD cues are processed not only after information is passed to the dorsal stream but also affect streaming at various earlier stages (at 60-90 ms and at 150-250 ms) that are concurrent with the earliest stages of cortical ITD processing (e.g., Spierer et al 2008;Tardif et al 2006), and even partially precede the differential processing of pitch vs ITD cues ).…”
Section: The Interaction Between Semantic and Spatial Information -Evmentioning
confidence: 99%
“…Using EEG and MEG to measure brain activity in human listeners, we have found that the hearing out of dichotic pitches elicits a sequence of auditory cortical responses over a time window of some 150-400 ms after the onset of a dichotically-embedded pitch. In a series of experiments (Johnson et al, 2003;Hautus & Johnson, 2005;Johnson et al, 2007;Johnson & Hautus, 2010) we have shown that these responses correspond to functionally distinct stages of auditory scene analysis. Our data provide new insights into the nature, sequencing and timing of those stages.…”
Section: Introductionmentioning
confidence: 95%